Pemaparan Isu Malaysia-indonesia Dalam Portal Media Dan Televisyen Indonesia: Satu Analisis Semiotik Sosial Visual - Bharata, Bonaventura Satya (2022)
Conflict between Indonesia and Malaysia began since the 1950s and in the beginning of 2000 tensions due to various issues such as borders, migrant workers, culture and haze continued to increase. Past studies have shown that the mass media, especially in Indonesia, is the source of this controversy through sometimes unbalanced reporting. The purpose of this study is to examine the content of the Indonesian mass media in interpreting the relationship with Malaysia in the borders issue, migrant workers, culture and haze from 2008-2018. It is done by analyzing the signs and meaning of the news, as well as evaluating the process of producing news about Malaysia in Metro TV, Televisi Republik Indonesia (TVRI), Kompas.Com and AntaraNews.Com news portals. A total of 320 news texts from the four media were analyzed and followed by interviews with 8 (eight) journalists and media editors involved. All data were analyzed using visual social semiotics method and guided by two theories namely the construction of social reality and newsroom culture. The findings of the study showed that all four media interpreted Malaysia as a country that always looking for trouble with Indonesia in all four issues studied. Metro TV and TVRI have similar interpretations of Malaysia in all the four issues which are Malaysia is an arrogant country or nation, often creates problems at the border, steals Indonesia's natural resources and culture, tortures Indonesian migrant workers and does not want to take responsibility about the haze issue while Malaysian companies in Indonesia are the cause of forest fires.